Effect of indapamide/perindopril fixed-dose combination on 24-hour blood pressure and cognitive functions in treatment-naive middle-aged patients with essential arterial hypertension - T. M. Ostroumova; V. A. Parfenov; O. D. Ostroumova; E. V. Borisova (Неврология, нейропсихиатрия, психосоматика)
Objective: to investigate the effect of indapamide/perindopril fixed-dose combination (FC) on 24-hour blood pressure (BP) and cognitive functions in antihypertensive treatment-naive middle-aged patients with uncomplicated grade 1–2 essential arterial hypertension (EAH) . Patients and methods. The open prospective study enrolled 25 patients (9 men and 16 women) aged 40–59 years with a diastolic BP of 90–109 mm Hg and/or a systolic BP of 140–179 mm Hg, as evidenced by routine measurements. As starting antihypertensive therapy, the patients received indapamide 1.25/perindopril 5 mg FC once daily in the morning; if necessary, after 2 weeks (if the routine blood pressure was ≥140/90 mm Hg) they took indapamide 2.5/perindopril 10 mg once daily in the morning. The follow-up period was 14–16 weeks. Before and at the end of the follow-up, the patients underwent 24-hour ambulatory BP monitoring (ABPM) and evaluation of cognitive functions using the Montreal Cognitive Assessment (MoCA), ten-words test (immediate and delayed word recall), verbal association test (literal and categorical associations), number connecting test (Trail making test (TMT), part A and numbers and letters connecting test (TMT) part B), and Stroop test. Results. At the end of the follow-up period, treatment with indapamide/perindopril fixed-dose combination showed a statistically significant reduction in BPs, as evidenced by routine measurements and ABPM (during 24-hour, and awake and sleep periods); a statistically significant cognitive improvement: an increase in the number of the so-called words in the ten-words test during both immediate (from 5.5±1.6 6.5±1.5 words; p=0.02 vs baseline) and delayed (from 6.2±1.7 to 7.4±1.4 words; p=vs baseline) recalls, a decrease in the performance time of TMTB (from 112.6±42.5 to 90.4±28.4 sec; p=0.02) and Stroop test Part 3 (from 135.5±50.1 to 112.6±19.6 sec; p=0.02), and a larger number of called words in the categorical associations test (from 6.5±2.4 to 8.1±2.9 words; p=0.02). Conclusion. The results obtained indicate that in treatment-naive middle-aged patients with EAH, indapamide/perindopril fixed-dose combination assures an effective reduction in BPs, as evidenced by routine measurements and ABPM, also improves cognitive functions, particularly attention, information processing speed, semantic memory, cognitive flexibility, and short-term and long-term memory.